2011
DOI: 10.1016/j.bbadis.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal metabolism flexibility in response to high palmitate concentrations in myotubes derived from obese type 2 diabetic patients

Abstract: Insulin resistance in type 2 diabetes (T2D) is associated with intramuscular lipid (IMCL) accumulation. To determine whether impaired lipid oxidation is involved in IMCL accumulation, we measured expression of genes involved in mitochondrial oxidative metabolism or biogenesis, mitochondrial content and palmitate beta-oxidation before and after palmitate overload (600μM for 16h), in myotubes derived from healthy subjects and obese T2D patients. Mitochondrial gene expression, content and network were not differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 56 publications
4
41
1
Order By: Relevance
“…Thus, in spite of the fact that there was no difference in OCR between obese non-diabetic myotubes and post-diabetic myotubes when differentiated in LG or HG, the GAL media was able to highlight a decreased oxidative capacity in post-diabetic myotubes compared to obese non-diabetic myotubes. Other studies have described a decrease in oxidative metabolic capacity in myotubes derived from diabetic patients as indicated by a decrease in citrate synthase activity [7] and a decrease in lipid oxidation capacity [5], [9]. Myotubes derived from post-diabetic subjects are also known to have a decreased oxidative capacity when challenged with a high glucose medium (decreased mitochondrial content, decreased citrate synthase and COX activities) compared to myotubes derived from matched obese non-diabetic individuals [40].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, in spite of the fact that there was no difference in OCR between obese non-diabetic myotubes and post-diabetic myotubes when differentiated in LG or HG, the GAL media was able to highlight a decreased oxidative capacity in post-diabetic myotubes compared to obese non-diabetic myotubes. Other studies have described a decrease in oxidative metabolic capacity in myotubes derived from diabetic patients as indicated by a decrease in citrate synthase activity [7] and a decrease in lipid oxidation capacity [5], [9]. Myotubes derived from post-diabetic subjects are also known to have a decreased oxidative capacity when challenged with a high glucose medium (decreased mitochondrial content, decreased citrate synthase and COX activities) compared to myotubes derived from matched obese non-diabetic individuals [40].…”
Section: Discussionmentioning
confidence: 98%
“…Cell culture of human primary myotubes offers not only an excellent and dynamic model for studying metabolism under standardized conditions, but provides an excellent system for studying metabolic disorders. Indeed, a number of studies have shown that human primary muscle cells retain the same metabolic phenotype as those previously evidenced in vivo in muscle [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11]. The oxidative capacity of skeletal muscle is highly influenced by various genetic and environmental factors; cultured myotubes offer a unique model that separates these two influences on metabolic phenotype [7].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…palmitate-overloading impaired b-oxidation and promoted intramyocellular lipid accumulation in myotubes from patients with T2DM compared with controls (37). In order to examine the time course of FFA-dependent changes in insulin sensitivity and mitochondrial plasticity, we monitored whole body glucose uptake (Fig.…”
Section: Jelenik and Rodenmentioning
confidence: 99%
“…Gene expression analyses in the skeletal muscle identified several candidates involved in carbohydrate and lipid metabolism, namely pyruvate dehydrogenase kinase 4, fructose-1,6-bisphophatase 2, and carnitine palmitoyltransferase 1b, which could be involved in the additive effects of the combined intervention [53]. On the contrary, myotubes from T2D patients when challenged with high concentrations of palmitate show a defect in palmitate b-oxidation, and this impaired response could be the result of a lack of inhibition of ACC activity by the fatty acid [54].…”
Section: Fatty Acids and Insulin Resistancementioning
confidence: 99%